Analysis Of Customer Satisfaction To Quality Of Service Using Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA) And Potential Gain In Customer Values (PGCV) - Utami, Lidia Dwi; Putra, Ibnu Widiasa; Nurrochman3, Reza; Fatahilah, Azhar; M.T. , Yani Iriani Dra. (International Journal of Psychosocial Rehabilitation, 2020)
X is a logistic courier & financial accounting service company. A metric to measure their customer satisfaction need to be identified to maintain their customer loyalty in a satisfactory level. Based on data acquired during the research, there were some major declining order (-26%) from customer between July 2019 - September 2019 from 617.602 to 454.045 orders. The objective of this research is to analyze PT. X quality of service level by using Customer Satisfaction Index (CSI) methods and Importance Performance Analysis (IPA). In addition, by using Potential Gain in Customer Value (PGCV) methods, improvement suggestion shall be determined. The result on quality of service level based on research conducted in PT. X using Customer Satisfaction Index (CSI) methods is 61.49%, which is under “Quite Satisfied” category. Subsequently, the data was analyzed by using Importance Performance Analysis (IPA) methods resulting in some attributes in first quadrant need to be focused for improvement; such as safety guarantee of damaged or lost items, prioritizing customer interest, provide good service, delivery speed, on time delivery guarantee, and employee provide fast and appropriate service. Furthermore, attribute improvements were prioritized using Potential Gain in Customer Value (PGCV) methods. The result of this methods will help PT. X to better understand which attribute need to be addressed first to increase their customer loyalty. The result from most to least important attributes are; safety guarantee of damaged or lost items, prioritizing customer interest, provide good service, delivery speed, on time delivery guarantee, tracking shipment, employee provide fast and appropriate service, employee trustworthiness, give a good response when customer raise a problem, competitive rates, employees behave friendly and polite, sufficient waiting room, provide solutions in term of delivery, cleanliness and proper service place, Ease payment and billing, and strategic location and easy to reach.